Relation between Liver Lipid Content and Plasma Biochemical Indicators in Dairy Cows - Batista, Chester Patrique; Castro, Sandra Marcela; Correa, Héctor Jairo; Schallenberger Gonçalves, Rodrigo; de Faria Vale, Stella; González, Félix (Acta Scientiae Veterinariae, 2020)
Background: The incidence of metabolic disorders in dairy cows has increased as a result of intensive production practices and genetic selection for milk yield. Among such disorders, liver lipidosis is very frequently observed and has significant negative effects on cow health and milk yield. Severe energy supply deficit causes high fat mobilization, resulting in rapid body condition loss and liver lipid infiltration, which cannot always be detected by known blood biochemical indicators. The main objective of the study was to determine possible associations of blood biochemical parameters with liver lipid infiltration severity in high-yield multiparous Holstein cows along prepartum and postpartum periods. Materials, Methods & Results: Fifty-four high-yield Holstein cows from a herd managed in a free-stall system in the northwest region of the state of Rio Grande do Sul, Brazil were evaluated. Cows were divided in two groups according to their physiological status. Group 1 included 19 prepartum cows, with an average milk yield of 44.7 L/d in the previous lactation, and 2.8 average parity, and Group 2 included 35 postpartum cows, with an average milk yield of 46.8 L/d in the previous lactation, and 2.5 average parity. The farm produced 10,000 kg milk per year, containing 3.5% of fat, 3.2% of protein and 4.7% of lactose. Total cholesterol (CH), plasma triglycerides (TGp), beta-hydroxybutyrate (BHB), albumin (ALB), non-esterified free fatty acids (NEFA) levels, and aspartate aminotransferase (AST) and creatine kinase (CK) activities were analyzed in the plasma and liver triglycerides (TGl) levels were determined in liver tissue samples.The SPSS statistical software was used for the statistical analyses. The obtained data were analyzed for normality by the Shapiro-Wilk test and for homoscedasticity by Bartlett test. Data were submitted to analysis of variance, and means were compared by the t-test (PROC TTEST). Pearson correlation test (PROC CORR) was used to compare the results between prepartum and postpartum cows, and between those with and without lipidosis.An overall incidence of 20% severe hepatic lipidosis was determined both in prepartum and postpartum cows. Positive significant correlations were obtained between days in milk (DIM) and AST (r= 0.43; P < 0.01), CH and TGp (r= 0.44; P < 0.01), TGl and AST (r=0.32; P < 0.05), NEFA and AST (r= 0.45; P < 0.01) and CK and AST (r= 0.447; P < 0.01). Negative significant correlations were detected between TGp and DIM (r= -0.45; P < 0.01), and between TGl and TGp (r= -0.30; P < 0.05). Discussion: Prepartum cows showed moderate fat infiltration in the liver, while 25.7% of postpartum cows presented severe lipidosis. AST values increased as lactation progressed, suggesting a greater tendency of liver damage, in early postpartum. The obtained CK values were within the reference range, except for the cows with hepatic lipidosis, indicating that the measured AST activity was originated from the liver and not from the muscle tissues. TGp, NEFA and AST values indicate the degree of fat mobilization and, possibly, liver infiltration, while TGl indicates fat infiltration in the liver. Although negative energy balance (NEB) may trigger lipolysis and some degree of hepatic lipidosis, plasma BHB values did not significantly increase. The obtained results show that the evaluated plasma parameters may be useful to establish guidelines for the identification of changes in the metabolic profile of dairy cows during different production stages, as well as measures for the prevention and control of metabolic disorders.